El desarrollo de la lectura a través de estrategias lúdicas en estudiantes de segundo año de Educación General Básica de la Escuela de Educación Básica José Félix Ayala. - Asqui Ashqui, Vilma Inés (2024)
The research “The Development of Reading through Playful Strategies in Second Year Students of Basic General Education at the José Félix Ayala School of Basic Education” focuses on the development of reading through play strategies, exploring how these activities can improve reading comprehension and promoting a taste for reading, the objective is to analyze the recreational strategies for promoting reading in second-year students of basic general education at the José Félix Ayala School of Basic Education. The methodology used is based on a mixed approach, establishing as a non-experimental research design, documentary research that proposes the collection of data through direct observation, and field research that directly collects the data through a survey, the levels Applied research focuses on exploratory, descriptive and correlational research, the instruments for data collection used a population of 3 teachers and 24 students. Results reveal both strengths and areas for improvement, highlighting progress in word identification and literal comprehension, but challenges in inferential comprehension and reading fluency persist. Teachers recognize the importance of playful strategies, although their application varies. Furthermore, the conclusions highlight the importance of skills such as decoding and comprehension, highlighting the effective use of playful strategies, such as games and interactive stories, to increase interest and participation.